Nexus Between Equity Pricing Models and Equity Price Fragility: Empirical Insights From Pakistan - Anser, Muhammad Khalid; Yusop, Zulkornain; Abbas, Shujaat; Ali, Sajid; Ahmad, Munir (Frontiers in Energy Research, 2022)
Purpose: The study tests conventional and behavioral pricing multifactor impact on price fragility from the equity market of Pakistan. Methodology: The positivist approach is used to deduct study rationale via probability sampling. At the same time, systematic sampling for data collection of PSX is tested in parallel to mean-variance random walk theory. Findings: The impact of conventional factors is significant on price fragility in the short run and vice versa in the long run. Specifically, herd behavior and disposition effects are found to be insignificant. But size, value, illiquidity, and price earning had a significant impact on price fragility in the short run. Limitations: The current research has not covered the desired scope of the topic due to time limitations, lack of harmony in corporate data on databases, and literature on price fragility being very scarce. Implication: In PSX, there is a need to develop a corporate culture to promote the standard modern financial practice to enhance financial productivity and sustainability. For corporate culture to be established, corporate governance boards should be established, and family governance systems should be replaced by an independent democratic board. Mispricing and arbitragers need serious control. Originality: The value of the research is that little research currently exists on about pricing multifactor impact on price fragility.